GENE EXPRESSION RELATED TO STEVIOL GLYCOSIDE SYNTHESIS PRODUCED IN Stevia rebaudiana (Bert.) SHOOT CULTURE INDUCED WITH RED LED LIGHT IN TIS RITA BIOREACTOR SYSTEM - CHRISTELA MELVIANA (21116028), AGUSTINE
Stevia leaves contain steviol glycosides estimated to be 300 times sweeter than sucrose so that it is potential for natural sweetener in food industry. However, it’s in vivo propagation faced many obstacles, therefore in vitro methods is needed. To produce large quantity of stevia biomass in relatively short period method, i.e by using RITA (Recipient for Automated Temporary Immersion System). Production of stevioside is also limited as plants developing flowers. Manipulation using far-red light LED in Stevia rebaudiana culture system has been proven not only inhibiting flowering, but also increase biomass and steviol glycosides content. Far-red light LED was given during dark period of plant to interrupt the activity of phytochrome B. The inactive phytochrome inhibits the transcription regulation of locus T gene and LFY (Leafy) gene, thus prevents plants to flowering. Consequently, it was expected that the ent-kaurene acid precursors would lead to the production of a higher steviol glycosides. This study was conducted to evaluate the effect of far-red light LED on biomass growth, steviol content, and expression level of several genes which related to the synthesis of steviol glycosides and it’s derivatives, specifically ent-KO, ent-KS, ent-KAH 13, UGT85C2, UGT74G1 also UGT76G1 in TIS RITA bioreactor system. The result showed that the increase of biomass in far-red LED RITA was 1.702±0.114 g while in control RITA system (no exposure) was only 0.953±0.093 g. The productivity of S. rebaudiana in the far-red LED RITA system was 0.246 g.Lmedium-1.day-1, whereas in control RITA only 0.150 g.Lmedium-1.day-1. Additionally, the pattern of sucrose, mineral, and inorganic compounds consumption followed the growth of plant biomass for both systems. The gene expression profiles which were analyzed by using real-time PCR showed that plantlet exposed to far-red light LED have an increase expression levels in ent-KO gene (1.16 times), ent-KS1 (1.27 times), ent-KAH 13 (1.28 times), UGT85C2 (1.25 times), UGT74G1 (1.77 times) and UGT76G1 (1.14 times). The content of stevioside and rebaudioside-A contents in far-red LED RITA was higher 37.15% and 22.99% when compared to planlet cultured in RITA Controls.